PROMOTING EQUITY IN HEALTH THROUGH RESEARCH AND UNDERSTANDING - BARBARA STARFIELD (Developing World Bioethics Volume 4 Number 1 2004, 2004)
Developing strategies to reduce inequities in health requires an understanding of how inequities occur, determining the salient factors in their production, and deciding which ones are most amenable to change. The recognition of several principles regarding the manifestations and genesis of inequities can help to decide on strategies. In making decisions, it is important to consider whether the aim is to reduce disparities in the occurrence of ill health or to reduce disparities in the severity (including comorbidity, disability, dysfunction and fatality) of ill health. Evidence shows that the major impact on equity of health services, particularly regarding their potential to reduce severity, is attributable to the strength of primary care resources and services in communities and countries. Virtually every influence on the genesis of inequities is determined by the political context in which policy is made. The issue of health services is not different in this regard from other types of strategies. There is no longer any doubt about the pervasive influence of social factors on health. Almost two centuries of descriptive research provides convincing evidence of associations between social structures and relationships and health status in all countries and in all societies; if there is anything new from more recent research, it is that the association is not limited to differences between the lowest social strata and other social strata. Rather, the association is noted throughout the social spectrum. That is, there is a social gradient in health such that, for many if not most manifestations of ill health, the lower the social stratum, the worse the health. The challenge for the future is to understand why this is the case, to create a consensus that these inequalities are unnecessary and unacceptable, and to devise strategies that are both effective and possible. This paper will focus on the first of these aims, in a context that facilitates attention to the second and third aims.